2013
DOI: 10.1097/rli.0b013e3182a2af82
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Antegrade Pyeloperfusion to Protect the Renal Pelvis in Kidney Microwave Ablation Using an In Vivo Swine Model

Abstract: In MWA, cooled antegrade pyeloperfusion is not useful to modulate the ablation volume in peripheral or central locations. Accordingly, pyeloperfusion may not be useful as a protective measure to avoid thermal damage in MWA of the kidney. Therefore, MWA of central renal tumors does not seem advisable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, Margulis et al and Hwang et al [24,25] showed in animal models that pyeloperfusion did not significantly affect ablation size in a comparison of in vivo RFA of normal kidney. Regarding MWA, Isfort et al [26] team showed in porcine models no impact on the ablation volume with pyeloperfusion even though internal cooling had no effect on reducing thermal damage on the renal pelvis in either peripheral or central lesions. This might be due to the adoption of an anterograde instead of retrograde pyeloperfusion technique which could not assure a higher flow rate of cooling solution and a more efficient cooling effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, Margulis et al and Hwang et al [24,25] showed in animal models that pyeloperfusion did not significantly affect ablation size in a comparison of in vivo RFA of normal kidney. Regarding MWA, Isfort et al [26] team showed in porcine models no impact on the ablation volume with pyeloperfusion even though internal cooling had no effect on reducing thermal damage on the renal pelvis in either peripheral or central lesions. This might be due to the adoption of an anterograde instead of retrograde pyeloperfusion technique which could not assure a higher flow rate of cooling solution and a more efficient cooling effect.…”
Section: Discussionmentioning
confidence: 99%
“…Microwave ablation is an emerging alternative to radiofrequency (RF) ablation, for its merits of a more homogeneous temperature distribution, and broader energy deposition, as well as less susceptibility to heat-sink effects in the tumour targets [29]. To address the challenge of incomplete ablation and subsequent neoplasm recurrence; however, combinatory or synergistic strategies for MW ablation are still of great necessity.…”
Section: Discussionmentioning
confidence: 99%
“…Image-guided thermal or energy-based ablation technologies, such as radiofrequency (RF), microwave, laser, cryosurgery and high-intensity focussed ultrasound (HIFU), are emerging as alternatives treatments for cancer and have been used in the treating numerous types of tumours located in various tissues, including the liver, kidney, lung, uterine fibroids, bone, prostate, breast and adrenal glands [1][2][3][4]. Currently, percutaneous radiofrequency ablation (RFA) and microwave ablation (MWA) are the two most common modalities used to treat tumours [5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the active heating zone is relatively small [8], and has been shown to create a heat-sink effect in the liver [9]. Image-guided MWA is a minimally invasive local therapeutic modality that destroys tumours within the body by thermal coagulation or protein denaturation [1,3,[10][11][12][13]. Since MWA does not rely on conducting electricity into the tissue, its application is not limited by increased impedance or charring, allowing for a larger ablation zone and shorter treatment times [6].…”
Section: Introductionmentioning
confidence: 99%